Impulsivity across the course of bipolar disorder - Strakowski, Stephen M. (2010)
OBJECTIVE: To determine whether abnormalities of impulse control persist across the course of bipolar disorder, thereby representing potential state markers and endophenotypes. METHODS: Impulse control of 108 bipolar I manic or mixed patients was measured on three tasks designed to study response inhibition, ability to delay gratification, and attention; namely a stop signal task, a delayed reward task, and a continuous performance task, respectively. Barrett Impulsivity Scale (BIS-11) scores were also obtained. Patients were then followed for up to one year and re-assessed with the same measures if they developed depression or euthymia. Healthy comparison subjects were also assessed with the same instruments on two occasions to assess measurement stability. RESULTS: At baseline, bipolar subjects demonstrated significant deficits on all three tasks as compared to healthy subjects, consistent with more impulsive responding in the bipolar manic/mixed group. In general, performance on the three behavioral tasks normalized upon switching to depression or developing euthymia. In contrast, BIS-11 scores were elevated during mania and remained elevated as bipolar subjects developed depression or achieved euthymia. CONCLUSIONS: Bipolar I disorder patients demonstrate deficits on laboratory tests of various aspects of impulsivity when manic, as compared to healthy subjects, that largely normalize with recovery and switching into depression. However, elevated BIS scores persist across phases of illness. These findings suggest that impulsivity has both affective-state dependent and trait components in bipolar disorder.